Odpowiedź:
a) 1 [tex]\frac{2}{3}[/tex] : 2 [tex]\frac{1}{2}[/tex] + 9 · [tex]\frac{1}{6\\}[/tex] = [tex]\frac{5}{3}[/tex] : [tex]\frac{5}{2}[/tex] + 9 · [tex]\frac{7}{6}[/tex] = [tex]\frac{5}{3}[/tex] · [tex]\frac{2}{5}[/tex] + 3 · [tex]\frac{2}{7}[/tex] = [tex]\frac{1}{3}[/tex] · 2 + [tex]\frac{21}{2}[/tex] = [tex]\frac{2}{3}[/tex] + [tex]\frac{21}{3}[/tex] = [tex]\frac{67}{6}[/tex]
b) ( 1 [tex]\frac{1}{2}[/tex] [tex])^{2}[/tex] - 1 [tex]\frac{3}{5}[/tex] : 2 [tex]\frac{2}{3}[/tex] = ( [tex]\frac{3}{2}[/tex] [tex])^{2}[/tex] - [tex]\frac{8}{5}[/tex] : [tex]\frac{8}{3}[/tex] = [tex]\frac{9}{4}[/tex] - [tex]\frac{8}{5}[/tex] · [tex]\frac{3}{8}[/tex] = [tex]\frac{9}{4}[/tex] - [tex]\frac{1}{5}[/tex] · 3 = [tex]\frac{9}{4}[/tex] - [tex]\frac{3}{5}[/tex] = [tex]\frac{33}{20}[/tex]